Combining the IMM with second order debiased converted measurement for detonation control. (2017) - Wu, Panlong; Zhang, Xinyu; Cao, Hongjun
This paper combines the IMM algorithm with second order debiased converted measurement (IMM-SDCM) for parameters estimation of optimal detonation control. Mathematical models are established for optimal detonation delay control under arbitrary encounter conditions in missile coordinate. The IMM-SDCM algorithm filters the information which is converted from polar coordinates to Cartesian coordinates. At the same time, it eliminates the divergence caused by coordinate transform. The encounter feature of missile and target is analysed by using simulation calculations. Simulation results indicate that the application of this algorithm can improve the estimation accuracy of detonation delay.